History Repeats Itself: Repeat Queries in Yahoo's Logs - Teevan, Jaime; Adar, Eytan; Jones, Rosie; Potts, Michael (Proceedings of the 29th Annual ACM Conference on Research and Development in Information Retrieval (SIGIR 2006), Seattle, WA, 2006)
Thanks to the ubiquity of the Internet search engine search box, users have come to depend on search engines both to find and re-find information. However, re-finding behavior has not been significantly addressed. Here we look at re-finding queries issued to the Yahoo! search engine by 114 users over a year.